Comparison of techniques for tibial dyschondroplasia assessment in broiler chickens - Paz, Ibiara Correia de Lima Almeida [UNESP]; Mendes, Ariel Antonio [UNESP]; Takita, T S [UNESP]; Vulcano, Luiz Carlos [UNESP]; Guerra, P C; Wechsler, Francisco Stefano [UNESP]; Garcia, R G [UNESP]; Takahashi, S E [UNESP]; Moreira, J [UNESP]; Pelícia, K [UNESP]; Komiyama, C M [UNESP]; Quinteiro, R R [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
This study was carried out at Faculdade de Medicina Veterinária e Zootecnia, Universidade Estadual Paulista, Botucatu, SP, Brazil, with the objective of evaluating the efficacy of four techniques in the assessment of tibial dyschondroplasia lesions in broiler chickens. Four hundred Cobb male chicks were reared from 1 to 39 days of age. At 39 days, forty birds were selected and tibial dyschondroplasia status was assessed by four different techniques: evaluation using the lixiscope, macroscopic examination, histological examination and bone mineral density assessment using optical radiographic densitometry. The efficacy of each technique to assess dyschondroplasia lesions in the tibial growth plate was determined in comparison to histology, which was considered to be 100% efficient. The correlation results between lixiscope analysis and histology were poor. Macroscopic scores and densitometry readings were highly correlated with histology scores, and it is considered that these techniques reliably reproduce the status of the growth plate.
Keywords: histology; lixiscope; macroscopic lesions; optical radiographic densitometry; tibial dyschondroplasia